Studi Literatur Kecerdasan Buatan untuk Audit: Kolaborasi atau Ancaman Bagi Profesi Auditor? - Alifia Mutiara Rachmawati; Tarenza Noviandari; Michael Revelin Ervan Septian; Tri Ratnawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Artificial intelligence is one of the fields of study of intelligent thoughts that can be used as a form to perform a calculation. This article aims to know artificial intelligence for auditing: collaboration or threats to the auditor profession. This article is a qualitative descriptive with a literature study. The result of this article is that artificial intelligence is a collaboration for the auditor profession because artificial intelligence makes it easier for auditors to carry out audit work in addition, artificial intelligence cannot be fully carried out without the role of an auditor because there is a process that must use the judgment of an auditor and cannot be taken over with technology.